Improved Bottleneck Bandwidth and Round-Trip Propagation Congestion Control Algorithm for Round-Trip Time Fairness - Zhao, Zhicheng; Cao, Weihua (Journal of advanced computational intelligence and intelligent informatics, 2023)
Traditional congestion-control algorithms based on packet loss are more favorable for short round-trip time (RTT) flows. However, when the flow occupies the bottleneck bandwidth, the effect of bottleneck bandwidth and round-trip propagation time (BBR) congestion-control algorithm is on contrary. A short RTT flow may become “starved” after multiple iterations, which leads to a significant fairness problem in the BBR. This study analyzed the convergence using the BBR algorithm principle and the effect of RTT on fairness. Thereafter, we proposed an improved algorithm termed BBR-f, constructed an inverse proportional function of RTT, and added a gain function to the congestion window (CWND) gain. A simulation experiment using the ns-3 network simulator platform shows that the algorithm can optimize fairness and improve bottleneck-linked bandwidth utilization. Finally, the Jain fair index was used to evaluate its effectiveness, and a comparison experiment with traditional algorithms was performed to verify the efficiency of the proposed method.